2017
DOI: 10.3126/jaar.v3i2.16754
|View full text |Cite
|
Sign up to set email alerts
|

Role-stress and mental health of government officers of Nepal

Abstract: S

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
0
1
Order By: Relevance
“…The job satisfaction among employees in this study was seen as lower than that in previous studies (Mishra & Shrestha 2019, Sapkota et al 2019. Stress has a negative effect on mental health (Rayamajhi 2016). This research also showed that stress decreased satisfaction.…”
Section: Discussioncontrasting
confidence: 74%
“…The job satisfaction among employees in this study was seen as lower than that in previous studies (Mishra & Shrestha 2019, Sapkota et al 2019. Stress has a negative effect on mental health (Rayamajhi 2016). This research also showed that stress decreased satisfaction.…”
Section: Discussioncontrasting
confidence: 74%